Counterexamples to the conjecture on stationary probability vectors of the second-order Markov chains - Saburov, Mansoor; Yusof, Nur Atikah (Elsevier Science Inc, 2016)
It was conjectured in the paper “Stationary probability vec-tors of higher-order Markov chains” (Li and Zhang, 2015[7])that if the set of stationary vectors of the second-order Markov chain contains k-interior points of the (k−1)-dimensional face of the simplex Ωnthen every vector in the (k−1)-dimensional face is a stationary vector. In this paper, we provide coun-terexamples to this conjecture.